Light Refraction by Water as a Rationale for the Poggendorff Illusion. (January 2017) - Bozhevolnyi, Sergey I.
The Poggendorff illusion in its classical form of parallel lines interrupting a transversal is viewed from the perspective of being related to the everyday experience of observing the light refraction in water. It is argued that if one considers a transversal to be a light ray in air and the parallel lines to form an occluding strip of a medium with the refractive index being between that of air and water, then one should be able to account, both qualitatively and quantitatively, for most of the features associated with the Poggendorff illusion. Statistical treatment of the visual experiments conducted with seven participants, each analyzing 50 configurations having different intercepting angles and strip widths, resulted in the effective refractive index of the occluding strip N  = 1.13 ± 0.15, which is sufficiently close to the average (between that of water and air) refractive index of ∼1.17. It is further argued that the same mechanism can also be employed to account for many variants of the Poggendorff illusion, including the corner-Poggendorff pattern, as well as for the Hering illusion.